Chemoprevention of oral cancer: Green tea experience - Ramshankar, Vijayalakshmi (Medknow Publications & Media Pvt Ltd, 2014)
Oral cancer has a well characterized progression from premalignant oral epithelial changes to invasive cancer, making oral squamous cell carcinoma an optimal disease for chemoprevention interventions prior to malignant transformation. The primary goal of chemoprevention here is to reverse, suppress, or inhibit the progression of premalignant lesions to cancer. Due to the extended duration of oral pathogenesis, its chemoprevention using natural products has been found promising due to their decreased dose and limited toxicity profiles. This review discusses with an emphasis on the clinical trials using green tea extract (GTE) in chemoprevention of oral premalignant lesions along with use of GTE as a chemopreventive agent in various other cancers as well. It is worthwhile to include green tea extract in an oral screening program for evaluating the premalignant lesions comparing the results between the treated and untreated group. Given the wide acceptance of green tea, its benefits may help in effective chemoprevention oral cancer.